If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 122 + -3x = 15x + 20 Reorder the terms: 122 + -3x = 20 + 15x Solving 122 + -3x = 20 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 122 + -3x + -15x = 20 + 15x + -15x Combine like terms: -3x + -15x = -18x 122 + -18x = 20 + 15x + -15x Combine like terms: 15x + -15x = 0 122 + -18x = 20 + 0 122 + -18x = 20 Add '-122' to each side of the equation. 122 + -122 + -18x = 20 + -122 Combine like terms: 122 + -122 = 0 0 + -18x = 20 + -122 -18x = 20 + -122 Combine like terms: 20 + -122 = -102 -18x = -102 Divide each side by '-18'. x = 5.666666667 Simplifying x = 5.666666667
| 4(2x-8)-2=4(x-4)+6 | | 2x+28=9x-28 | | 3(4x-1)=48 | | 0.4(x-4)=7.2 | | 4xy^4-32xy=0 | | -9(x-4)-3=46 | | 0.5x-0.1(5-x)=2.2 | | 77/121 | | -7-6=7-8x | | -3(2x+1)=21 | | 5(4x-3)=11 | | 4y^3+12y^2+5y=0 | | 23=49-7x | | f(x)=x^3-2x^2+2x-6 | | 20-9w=4(15-1w) | | 11+9lnx=6 | | y+11=19 | | 9p+-5=1 | | 5x=81.2 | | 2x^2=-5x-10 | | z^(-3)/z^(-7) | | 87=2x-3(5x-3) | | -4(-2+2x)=-32 | | (9m-15)6=18 | | x^2-2x-15/6x^2-54 | | 5x^2+7x=4 | | -4(-4-6x)=88 | | 3x-8=58-2x | | 3(4x-1)-7x=16 | | 5x+26+14x=82 | | 2x^2+8=32 | | 3^(-4)/3 |